Rainbow family collections selecting and using children's books with lesbian, gay, bisexual, transgender, and queer content - Naidoo, Jamie Campbell (Santa Barbara, Calif. Libraries Unlimited, 2012)
"This book examines and suggests picture books and chapter books presenting LGBTQ content to children under the age of 12--it's one of the only available resources to provide this important information"--Provided by publisher.
"Rainbow Family Collections examines over 200 children's picture books and chapter books with LGBTQ content from around the world. Highlighting titles for children from infancy to age 12, each entry in Rainbow Family Collections supplies a synopsis of the content, lists awards it has received, cites professional reviews, and provides suggestions for librarians considering acquisition. The book also provides a brief historical overview of LGBTQ children's literature along with the major book awards for this genre and a list of criteria for selecting the best books with this content. Interviews with authors and key individuals in LGBTQ children's book publishing are also featured"--Provided by publisher.
Understanding rainbow families -- Library services to rainbow families -- Overview of LGBTQ children's literature -- Book awards for LGBTQ children's literature -- Building a collection of children's materials reflecting LGBTQ content -- Picture books -- Chapter books -- Informational books, biographies, and LGBTQ children's media -- Resources for educators, librarians, and rainbow families.
Includes bibliographical references and indexes.
Keywords: Sexual minorities -- Juvenile literature -- Bibliography; Children of sexual minority parents -- Books and reading -- United States; Children's libraries -- Collection development -- United States; Libraries -- Special collections -- Sexual minorities; Children's libraries -- Services to minorities -- United States; Libraries and sexual minorities -- United States; Sexual minorities in literature; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / Collection Development; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / School Media; EDUCATION / Professional Development